Approximation by Kantorovich-Szász Type Operators Based on Brenke Type Polynomials. (1st December 2016) - Atakut, Çiğdem; Büyükyazıcı, İbrahim
ABSTRACT: In this article, we give a generalization of the Kantorovich-Szász type operators defined by means of the Brenke type polynomials introduced in the literature and obtain convergence properties of these operators by using Korovkin's theorem. Some graphical examples using the Maple program for this approximation are given. We also establish the order of convergence by using modulus of smoothness and Peetre's K -functional and give a Voronoskaja type theorem. In addition, we deal with the convergence of these operators in a weighted space.